A multilevel dynamic model for documenting, reactivating and preserving interactive multimedia art - Fiordelmondo, Alessandro; Russo, Alessandro; Pizzato, Mattia; Zecchinato, Luca; Canazza, Sergio (Frontiers in Signal Processing, 2023)
During the last years, preservation of interactive multimedia artworks has become a growing research field. In fact, the role played by multimedia within the performing arts has become more and more important, thanks to the development of new technologies. Nevertheless, technologies inevitably face issues related to obsolescence of devices, operating systems etc. In dealing with interactive multimedia artworks, consolidated preservation strategies are inadequate, because they don't cover the complex relations between analogue and digital components that can be used for the realization of the artwork. Therefore, there is the need to develop a preservation model capable of preserving analogue and digital components, as well as the experience and the human interaction, in compliance with the intent of the artist. This work presents the multilevel dynamic preservation (MDP) model, developed at the Centro di Sonologia Computazionale (CSC) of the Department of Information Engineering of the University of Padova. In the last part of this work, the proposed model is applied to the reactivation of the Il caos delle sfere, a 1999 installation by Italian composer Carlo De Pirro. The overall reactivation process of the artwork aimed at preserving its identity, rather than simply replicating the original performance. For this purpose, before proceeding with the reactivation of the artwork, several approaches were investigated, in order to choose the more suitable one. Given the complexity of the artwork, it has been chosen to proceed with a hybrid approach, since a technology migration was necessary for the communication node, while for other components (i.e. the pinball and the Disklavier piano) it was possible to proceed with a ”purist” approach. The reactivation of the artwork produced new documentation, that filled the gap in the existing one. In fact, the documentation process covers a central role in the proposed model, both for preserving and reactivating the artwork.